Struktur dan Ideologi Teenlit Karya Dyan Nuranindya - Titi Wuryani; Agus Nuryatin; Mimi Mulyani (STKIP Singkawang, 2018)
This study aims to describe the structure and ideology of Dyan Nuranindya's work. There are six teenlit works by Dyan Nuranindya, namely Dealova, Star Secret, Canting Cantiq, Cinderela Pink Hair, Rock N Roll Onthel, and Kotak Pelangi. The method used in this research is descriptive analysis and dialectic which is also part of the approach of theory of genetic structuralism. The data in the study of the parts of the text in the form of words, phrases or sentences related to the genetic structure, ideology in the work of Dyan Nuranindya's work. The results showed the structure of literary works by Dyan Nuranindya's literature includes hero store relationships with other figures, and oposional relations. Relation of hero characters with other characters include brother's sister relation, parent's relation with child, love relation, oposional relation. The ideology contained in the work of Dyan Nuranindya's work is to achieve the ideals, love the homeland, preserve nature.